Diversificação produtiva em agroecossistemas familiares nos municípios de Santa Maria das Barreiras e Conceição do Araguaia, Pará - NOGUEIRA, Ana Caroline Neris (Universidade Federal do Pará, 2021)
This study aimed to evaluate the process of diversification of agroecosystems located in the southern portion of Pará, departed from the sample that participated in the projects that the CPT performed in order to guarantee the food sovereignty of the settler families by offering diversified products and conservation environmental awareness courses with the use of fire as a management and the effect of specialization in cattle raising and training courses on the implementation of productive activities. These initiatives have started a phase where the context for the establishment of diversification was unfavorable, that due to lack of public policies, low investment capacity of farmers and cattle farming on the forest. At this stage, there have been farmers who chose to diversify, some have managed to maintain diversification, but others did not carry on activities. Subsequently, the second phase of the historical region that began late in the 1990s, enabled a larger opening investment of the federal government, through public policies that started to incorporate the family farm, PRONAF (founded in 1996) was a good example. Even in this more favorable context was not possible for many families opt for diversification and not that they were able to maintain their productive activities.To understand the factors that led to withdrawal or that favored the installation of diverse projects is necessary to go beyond the aspects extra lot to understand the peculiarities of each situation, as well as projects of the family are crucial to understanding this process. The assessment of sustainability wide agroecosystems was ensured by the use of the tool MESMIS, the indicators raised in the environmental, social and economical solution showed a high diversity of realities, the best performance among the agroecosystems of the two phases, is in the 1st phase of history the region and the worst performances in the 2nd phase of dynamic change in production, it strengthens the internal aspects of agroecosystems, their limitations and strengths are crucial to the success or failure of diversification. The size was a more fragile environment, some families do not have the native area, or the entry by fire or livestock feed. In the social dimension, the labor was the most significant indicator, as in the technical-economic indicators most significant were the efficiency of management (limitation, income, productive diversity) and the current diversity of agroecosystems.